1992
DOI: 10.1128/jcm.30.4.905-910.1992
|View full text |Cite
|
Sign up to set email alerts
|

Infection of peripheral blood mononuclear cells and cell lines by cell-free human T-cell lymphoma/leukemia virus type I

Abstract: Previous studies of in vitro infection by human T-cell lymphoma/leukemia virus type I (HTLV-I) have required cocultivation of target cells with HTLV-I cell lines or vesicular stomatitis virus pseudotypes containing HTLV-I envelope proteins. We report here the development of a cell-free infection assay for HTLV-I. Target cells were incubated with purified, DNase-treated HTLV-I virions for 4 h at 37°C. Target cell DNA was then analyzed for the presence of newly synthesized HTLV-I proviral DNA by the highly sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
55
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(59 citation statements)
references
References 30 publications
4
55
0
Order By: Relevance
“…These findings indicated that c77 cells produced highly transmissible HTLV-1 and the infectivity of the c77 cell supernatant was estimated to be more than 3,000 times higher than that of the culture supernatant derived from MT-2, C91 /PL or HOS/PL cells. Fan et al (1992) have detected HTLV-I-specific bands when indicator cells are infected with highly concentrated HTLV-I produced by MT-2 cells. This method has not apparently been used for titrating neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 94%
“…These findings indicated that c77 cells produced highly transmissible HTLV-1 and the infectivity of the c77 cell supernatant was estimated to be more than 3,000 times higher than that of the culture supernatant derived from MT-2, C91 /PL or HOS/PL cells. Fan et al (1992) have detected HTLV-I-specific bands when indicator cells are infected with highly concentrated HTLV-I produced by MT-2 cells. This method has not apparently been used for titrating neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 94%
“…7) Furthermore, the somatic-cell hybrid cell line L1q, which contains human chromosome 17q, could be infected with HTLV-1, but the parental mouse fibroblast cell line, LMTK−, could not. 25) Thus, the receptor gene for HTLV-1 has been assigned to human chromosome 17q. 7,26,27) However, Sutton and Littman reported that HIV (HTLV-1) pseudotype virus could infect mouse fibroblast LMTK− cells at 4.5% efficiency and four other LMTK− cell lines which contained at least human chromosome 17q at 0.015-2.0% efficiency as compared to a human osteosarcoma cell line, HOS cells.…”
Section: Discussionmentioning
confidence: 99%
“…The possibilities include differences in the virus preparations, the target mouse cell lines and/or the sensitivity and specificity of the assay systems. The cell-free HTLV-1 used in earlier studies was mostly from MT-2 cells, 25,29,30) C91/PL cells 30) or HOS/PL cells. 31) The filtered virus in the culture fluids of C91/PL cells could infect human lymphocytes from cord blood and peripheral blood, and that of MT-2 cells could infect human lymphocytes from cord blood only, while that of C10/MJ could infect neither of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Fan et al developed a sensitive HTLV-1 infection assay with cell-free HTLV-1 pro-duced from MT-2 cells, only low levels of viral DNA have been detected. 20) Haraguchi et al reported that the cell-free HTLV-1 produced from a feline kidney cell line, c77, is highly transmissible to human cells. The transmission of cell-free HTLV-1 produced from c77 cells was estimated to be more than 3000 times higher than that of HTLV-1 derived from MT-2, C91/PL or HOS/PL cells by PCR assay.…”
mentioning
confidence: 99%